An exploration of tools and methodologies for valuation of biodiversity and biodiversity resources and functions (The Secretariat MontrealCA, 2007)
Explores existing methodologies for valuation of biodiversity and biodiversity resources and functions, as well as other tools for prioritization in decision-making, by preparing a compilation of existing valuation tools that provide an overview of the discussion on their methodological status, if appropriate, as well as an assessment of their applicability in terms of effectiveness and capacity preconditions.
Keywords: BIODIVERSITY